THE INFLUENCE OF E-COMMERCE TO STUDENT ONLINE DECISION AT SAM RATULANGI UNIVERSITY - Rantung, Brenda C. V.; Massie, James D.D; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract:. This study objectives are to analysis the influence of convinience, e-word of mouth communication, trust also promotion on consumer online decision partially and simultaniously for students at Faculty Economics and Business Sam Ratulangi University. This research use university students as respondents. Sample of this research are 100 respondents. Data analysis using multiple regression analysis. This research finds:the research model consisting of: convinience, e-word of mouth communication, trust and promotion has a positive and significant influence on consumer online decision. Results of hypothesis testing found that convinience, e-word of mouth communication, trust and promotion partially has significant and positive impact on consumer online decision in this research. E-word of mouth communication has the highest impact variable that influence consumer online decision comparing to other variable. Suggestions: E-commerce corporation in this research must pay attention to this research finding. E-commerce organization in this research must improve variables that correlated to consumer online decision especially in university students.Â Keywords: convinience, e-word of mouth communication, trust, promotion, e-commerce, consumer online decision